Transcriptomic profiles of Florida pompano (Trachinotus carolinus) gill following infection by the ectoparasite Amyloodiniumocellatum. Issue 125 (June 2022) - Zhang, Dongdong; Mohammed, Haitham; Ye, Zhi; Rhodes, Melanie A.; Thongda, Wilawan; Zhao, Honggang; Jescovitch, Lauren N.; Fuller, S. Adam; Davis, D. Allen; Peatman, Eric
Abstract: The dinoflagellate Amyloodinium ocellatum is an important pathogenic parasite infecting cultured marine and brackish water fishes worldwide. This includes cultured Florida pompano ( Trachinotus carolinus ), which is one of the most desirable marine food fish with high economic value in the USA. A. ocellatum infects fish gills and causes tissue damage, increased respiratory rate, reduced appetite, and mortality, especially in closed aquaculture systems. This study mimicked the natural infection of A. ocellatum in cultured pompano and conducted a transcriptomic comparison of gene expression in the gills of control and A. ocellatum infected fish to explore the molecular mechanisms of infection. RNA-seq data revealed 604 differentially expressed genes in the infected fish gills. The immunoglobulin genes (including IgM/T) augmentation and IL1 inflammation suppression were detected after infection. Genes involved in reactive oxygen species mediating parasite killing were also highly induced. However, excessive oxidants have been linked to oxidative tissue damage and apoptosis. Correspondingly, widespread down-regulation of collagen genes and growth factor deprivation indicated impaired tissue repair, and meanwhile the key executor of apoptosis, caspase-3 was highly expressed (25.02-fold) in infected fish. The infection also influenced the respiratory gas sensing and transport genes and established hypoxic conditions in the gill tissue. Additionally, food intake and lipid metabolism were also affected. Our work provides the transcriptome sequencing of Florida pompano and provides key insights into the acute pathogenesis of A. ocellatum . This information can be utilized for designing optimal disease surveillance strategies, future selection for host resistance, and development of novel therapeutic measures. Highlights: Transcriptomes of Florida pompano gills after A. ocellatum infection. IL1 suppression and antibody augmentation were detected in infected fish. Infection caused oxidative stress, tissue damage and apoptosis in pompano gills.